Representations of OxyContin in North American Newspapers and Medical Journals - Emma Whelan; Mark Asbridge; Susan Haydt (Pain Research and Management)
Following the approval of OxyContin (Purdue Pharma, Canada) for medical use, the media began to report the use of OxyContin as a street drug, representing the phenomenon as a social problem. Meanwhile, the pain medicine community has criticized the inaccurate and one-sided media coverage of the OxyContin problem. The authors of this study aimed to contribute to an understanding of both sides of this controversy by analyzing the coverage of OxyContin in newspapers and medical journals. The analyses revealed inconsistent messages about the drug from physicians in the news media and in medical journals, which has likely contributed to the drug’s perception as a social problem. The authors suggest ways to address the lack of medical consensus surrounding OxyContin. The results of this study may help resolve the concerns and conflicts surrounding this drug and other opioids.